Testing-effort-dependent software reliability growth model for a distributed environment using debugging time lag functions. (1st January 2012) - Kapur, P.K.; Johri, Prashant; Khatri, Sunil Kumar
Distributed software system consists of reused and newly developed software components. This paper presents testing-effort-dependent Software Reliability Growth Model (SRGM) for distributed environment. We have used logistic learning function for newly developed components with the assumption that the skill of the testing team grows as testing progresses. We assume that detected faults are not immediately removed but lag the fault detection process by debugging time lag. Thus, different debugging time lag functions have been used during removal process for newly developed components. The proposed model has been validated and is shown that the proposed model results are comparatively better than the existing ones.